Os efeitos da pós pandemia na saúde mental de professores do ensino médio: um estudo realizado com docentes no município de Acará - OLIVEIRA, Tiffany Souza de (2025)
The purpose of this article isto discuss and reflect on the mental health of high school teachers in the aftermath of the pandemic. The objective isto analyze the testimonies of teachers who work in a State High School located in the municipality of Acará-PA, to verify the impacts of the pandemic on their professional life and mental health. The approach adopted is qualitative research, and the type of research is case study, aiming to delve deeper into the phenomenon studied. The bibliographical research and the high school teachers' reports revealed that there are sequels in their lives caused by the pandemic, both in their teaching work and in their mental health, affected by the rapid immersion they made in emergency remote teaching. The lack of support and resources to develop their work during the pandemic, the increase in work demands and the difficulties in mitigating the damage that the pandemic has caused to their students, have corroborated the increase in their levels of stress, tiredness and mental exhaustion.